Assessment of Antibody Response Elicited by a 7-valent Pneumococcal Conjugate Vaccine in Pediatric Human Immunodeficiency Virus Infection - Tarragó, David (American Society for Microbiology, 2005)
We investigated antibody responses against pneumococci of serotypes 6B, 14, and 23F in 56 children and adolescents with perinatal human immunodeficiency virus (HIV) infection who were vaccinated with 7-valent pneumococcal conjugate vaccine. Overall immune responses differed greatly between serotypes. Correlation coefficients between immunoglobulin G (IgG) measured by enzyme-linked immunosorbent assay (ELISA) and functional antibodies measured by a flow cytometry opsonophagocytosis assay (OPA) varied with serotype and time points studied. After 3 months of administering a second PCV7 dose we got the highest correlation (with significant r values of 0.754, 0.414, and 0.593 for serotypes 6B, 14, and 23F, respectively) but no significant increase in IgG concentration and OPA titers compared to the first dose. We defined a responder to a serotype included in the vaccine with two criteria: frequency of at least twofold OPA and ELISA increases for each serotype and frequency of conversion from negative to positive OPA levels. Responders varied from 43.9% to 46.3%, 28.5% to 50.0%, and 38.0% to 50.0% for serotypes 6B, 14, and 23F, respectively, depending on the response criterion. The present research highlights the importance of demonstrating vaccine immunogenicity with suitable immunological endpoints in immunocompromised patients and also the need to define how much antibody is required for protection from different serotypes, since immunogenicity differed significantly between serotypes.